Against the individual: critical attempts and Incomplete hypotheses - Yuing, Tuillang (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
This study elaborates a range of suggestions for a theoretical-philosophical balance of the notion of the "individual". In fact, in liberal social and political theory, the concept of the individual presents itself as being one of regular use. Nevertheless, in many cases it seems to be an insufficiently discussed notion and, therefore, one preventing a timely assessment of the arguments it pays homage to. Thus, here I first propose to question the creditworthiness of the notion of the individual as a holder or source for a “universal reason”. In this sense, the idea of the transcendental subject of knowledge possesses grey areas where the individual is neither owner nor sovereign of his representations. Second, following Roberto Esposito’s suggestions about Locke’s liberalism, I examine the notion of the individual understood as a postponement of the coming into being of the figure of the sovereign. Finally, I review Bruno Latour’s theses about the sociotechnical mediations constituting social collectives where the individual and the subject-object dichotomy are always a result rather than a foundation.